2018
DOI: 10.1108/bpmj-12-2016-0235
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between business process management (BPM) and accounting

Abstract: Purpose Multidisciplinary business process management (BPM) research can reap significant impact. We can particularly benefit from incorporating accounting concepts to address some of the key BPM challenges, such as value-creation and return on investment of BPM activities. However, research which addresses a relationship between BPM and accounting is scarce. The purpose of this paper is to provide a detailed synthesis of the current literature that has integrated accounting aspects with BPM. The authors profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…The research suggests that future developments in management accounting should focus on integrating more sociological-oriented aspects, such as the role of management accountants in facilitating innovation and supporting strategic decision-making in product development. Abeygunasekera et al (2018) explore the nexus between business process management (BPM) and accounting. They highlight the potential for multidisciplinary research that incorporates accounting concepts to address key BPM challenges, such as value creation and return on investment.…”
Section: Future Directions and Potential Innovations In Management Ac...mentioning
confidence: 99%
“…The research suggests that future developments in management accounting should focus on integrating more sociological-oriented aspects, such as the role of management accountants in facilitating innovation and supporting strategic decision-making in product development. Abeygunasekera et al (2018) explore the nexus between business process management (BPM) and accounting. They highlight the potential for multidisciplinary research that incorporates accounting concepts to address key BPM challenges, such as value creation and return on investment.…”
Section: Future Directions and Potential Innovations In Management Ac...mentioning
confidence: 99%
“…A review by Sánchez González et al (2010) examined measurement and found that only a small percentage of existing business process measures have been validated empirically. Another literature review identified a dearth of work linking the disciplines of BPM and accounting, as the reviewed literature reviewed primarily focused on performance measurement (Abeygunasekera et al , 2018).…”
Section: Theoretical and Conceptual Foundationmentioning
confidence: 99%
“…The relationship between process orientation and MC has been analyzed in management accounting research (Arai, 2021; Donnelly et al , 2021; Grasso and Tyson, 2021; Chenhall and Moers, 2015; Fullerton et al , 2013; Ferreira and Otley, 2009; Berry et al , 2009; Chenhall, 2008). Publications in disciplines such as operations (Bellisario and Pavlov, 2018; Fullerton et al , 2014), quality management (Eldridge et al , 2014) and business process management (BPM) (Abeygunasekera et al , 2018) also address this topic. However, there is a significant gap of knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…SMEs are at the centre of the proposals for policies that are debated in the countries of Africa. Notably, in Libya, the application of the so-called opening policies and conditions that characterise the productive apparatus regional mean factors should be considered to guarantee the stability of the SME (Abeygunasekera, Bandara, Wynn, & Yigitbasioglu, 2018). This situation is an obvious opportunity to take advantage of its strengthening.…”
Section: Introductionmentioning
confidence: 99%